Waste to Energy: Combustion, Performance, and Emission Characteristics of Waste Animal Fats/Diesel Blends Premixed with Various Alcohols as Port Fuels - Sathish, T.; Giri, Jayant; Saravanan, R.; Agbulut, Umit (WILEY-V C H VERLAG GMBH, 2024)
Animal flesh is a major food source with economic and industrial value for consumer demand. These meats produced biowaste during and after preparation and use. Chicken intestines make up most of the waste thrown away after processing or frying. This study considers it a biodiesel source. Transesterification turns chicken intestine waste fat oil into biodiesel. This oil is used in compression ignition (CI) engines but performs poorly compared to diesel. Diesel, the base fuel, is mixed with 20% biodiesel. The remaining 10% and 20% of butanol and pentanol are port fuels, improving combustion and lowering emissions in the 5.2 kW, 1500 rpm CI engine. 20% pentanol premixing outperformed butanol premixing, blending, and engine CIWFOB operation. The greater heating value improves combustion, therefore 20% pentanol premixing with blend produces 32.76% BTE, 10.57% more than diesel. It produced 55.18% less CO and 50.92% less smoke than diesel, which has a greater heat release rate (48.86 J/CAD) and peak pressure (64.76 bar). This premixing costs NOx emissions. The CIWFOB blend with 20% pentanol premixing improves engine performance. For SDGs 7, 9, 12, and 13, this study is supported. Waste animal fat is converted into alternative fuels for compression ignition engines, and the results regarding engine performance, combustion, and emission characteristics are discussed. The present research helps waste management and the usability of novel fuels as fuel substitutes. Also, this work supports attaining the Sustainable Development Goals (SDGs) of 7, 9, 12, and 13. image
Keywords: chicken fat biodiesel; combustion; port Fuels; waste management; waste to energy; Science & Technology - Other Topics